Pengaruh Daya Tarik Jingle Iklan Terhadap Brand Awareness Nivea Men Creme - Yufika Islamia Rizkiani; Salman (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Brand elements in the form of jingles (songs) can help the success of a product and brand, one of which is to increase brand awareness of a product. In this study the researchers wanted to find out whether there was an influence in the use of Nivea Men Creme Anthem advertise attractiveness towards Brand Awareness in the Badminton community Padjajaran University (UBTU). The theory employed in this investigation is the theory of stimulus and reaction. Trial, the simple linear regression test, the determination test, and the T test were utilized for data analysis. The study was conducted utilizing a questionnaire with 98 participants, and a pretest with 30 participants was conducted beforehand. The sample method employed is non-probability sampling with purposive sampling. According to the findings of this study, the beauty of YouTube Jingle advertisements for Nivea Men Creme has a 41,6% impact on Brand Awareness.